Diversity of Crustaceans in Intertidal Zone at Kukup Beach, Gunungkidul - Setyaningrum, Sri; Pangestuti, Azwa Yuliananda; Pasaribu, Callista Nadya Noel; Munajib, Ibnu Ainun; Camelia, Naely Muna; Azahra, Safaa; Judith, Tiara Putria; Eprilurahman, Rury (Nusantara Science and Technology Proceedings, 2025)
Indonesian waters are famous for their diversity of marine biota. Crustaceans are one of the many marine biota found, especially in the coastal intertidal zone. The waters off the south coast of Java are characterized by large waves and currents. Kukup Beach is one of the beaches located in the area of D. I. Yogyakarta with a flat and undulating beach shape with a narrow intertidal zone. Crustaceans have an important role in coastal ecosystems as bioindicators and omnivore predators. However, not many studies have been conducted to determine the diversity of crustaceans in Kukup Beach. The purpose of this research was to study and determine the diversity of crustaceans in the intertidal zone of Kukup Beach. Sampling and collection were conducted on March 11, 2023, with a systematic sampling method through a belt transect approach. The results showed that 8 families of Crustacea were found in Kukup Beach, namely Alpheidae, Majidae, Pilumnidae, Grapsidae, Portunidae, Oziidae, Xanthidae, and Diogenidae. The result of the calculation of the spesies richness index (R) of Crustacea in the intertidal zone at Kukup Beach was 3,69.